2013
DOI: 10.6061/clinics/2013(10)11
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of aqueous extracts of roselle (Hibiscus sabdariffa L. UKMR-2) against red blood cell membrane oxidative stress in rats with streptozotocin-induced diabetes

Abstract: OBJECTIVES:The aim of this study was to investigate the protective effects of aqueous extracts of roselle (Hibiscus sabdariffa L. UKMR-2) against red blood cell (RBC) membrane oxidative stress in rats with streptozotocin-induced diabetes.METHODS:Forty male Sprague-Dawley rats weighing 230-250 g were randomly divided into four groups (n = 10 rats each): control group (N), roselle-treated control group, diabetic group, and roselle-treated diabetic group. Roselle was administered by force-feeding with aqueous ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
3
11
0
4
Order By: Relevance
“…47-67 ISSN ( In the present study, STZ-treated rats showed reduced BW and alterations in glycemic parameters including hyperglycemia and reduction of serum insulin level. Our results are similar to previous studies described in the literature (Mohamed et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…47-67 ISSN ( In the present study, STZ-treated rats showed reduced BW and alterations in glycemic parameters including hyperglycemia and reduction of serum insulin level. Our results are similar to previous studies described in the literature (Mohamed et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…According to Waseem et al (2017), protein carbonylation indicates oxidative protein damage resulting from cisplatin-induced oxidative stress. PmEO100CP and BCP pre-treated rats significantly restored protein carbonyl content in the liver similar to the role of natural product on protein carbonylation previously shown by Mohamed et al (2013). 8-OHdG is the most significant indicator of DNA damage (Koyuncu et al 2017).…”
Section: Discussionsupporting
confidence: 78%
“…Hence continuously decreased serum antioxidant status or continuously increase oxidative status can catastrophically damage to the epithelial lining of lungs and allowing the movements of HP in the blood which can jeopardize the wellbeing of erythrocyte. In other study it was well demonstrated that RBC membrane of rats can't sustain the oxidative stress of streptozotocin-induced diabetes, however in the same study it was demonstrated that protective agent (antioxidants) when administer in adequate dose enables the RBC to sustain the oxidative stress of diabetes [18][19][20]. Cigarettes smoking has reached to alarming situation in all societies, irrespective of the gender and age.…”
Section: Discussionmentioning
confidence: 99%